Palliative care in cirrhotic patients: Brief summary of recent AASLD guidance - ÖZDOĞAN, OSMAN CAVİT (My University, 2022)
Palliative care in decompensated cirrhotic patients is a developing concept which should be used in cirrhotic patients during the advanced and terminal stages. Hepatologists and liver transplant teams mostly ignore the patients palliative care issues while intensively dealing with the liver diseases and its complications. This review is a brief summary of the recently published guidance discussing the palliative care, symptom based treatments and end of life with a collaborative and standartized approach which is recommended to all health care workers of cirrhotic patients.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Hepatoloji; Gastroenteroloji; Hepatology; Gastroenterology; AASLD guidance; decompansated cirrhosis; palliative care